Petroleum Products Pricing Reform in Nigeria: Welfare Analysis from Household Budget Survey - Adagunodo, Mathew (International Journal of Energy Economics and Policy, 2013)
This paper examines welfare effects of energy reform particularly petroleum products pricing reform in Nigeria. The data for 5000 households were collected to estimate a demand system for PMS, AGO and DPK. The survey contains information on the occupation and income of the household members, as well as on household expenditure and consumption as well as on a wide range of demographic and socio-economic characteristics. This study use marginal social cost approach to evaluate equity and efficiency implications of petroleum products subsidy reform in Nigeria. The reduction or removal of subsidy on PMS will save largest amount from government budget. When there is distribution concern, the marginal social cost of reducing subsidies on AGO is lowest supporting the reform that have been carried out by removing subsidies on AGO. However, marginal social cost for all petroleum products are extremely low suggesting reduction of subsidies on all petroleum products in Nigeria. These findings revealed that equity argument for continue subsidization of household kerosene can no longer be justified since marginal social cost is low. The reality is that apart from the NNPC outlets, there is no other outlet anywhere in Nigeria where kerosene is sold at the subsidised price. Keywords: petroleum products; subsidy reform; household’s welfare; expenditure elasticities; marginal social cost approach; Nigeria JEL Classifications: D12; Q4; Q41